The Extractive Industries Transparency Initiative (EITI) in Cameroon : realities and prospects - Munje, Ndansi Divine (2010)
For a long time, Cameroon was a success story in the context of Africa’s development. Unfortunately, the economic crises of the eighties and early nineties led to the failure of the development strategies that had been pursued until then, resulting in a severe deterioration of the country’s economy and the living standards of the Cameroonian people (Mentan, 2003). However, this country possesses significant oil wealth which if properly managed can generate abundant revenue to boost economic growth and fund anti-poverty measures. In 2005, Cameroon adhered to the Extractive Industries Transparency Initiative (EITI). A proper implementation of this initiative will improve transparency in the country’s oil sector and support national efforts against poverty and underdevelopment. In recent years though, donor organizations have made good governance and democracy cardinal conditions for the flow of development assistance (Degnbol-Martinussen and Engberg-Pedersen, 2003). A situation that has encouraged the proliferation of “pseudo” or “virtual” democracies across Sub-Saharan Africa (Diamond, 2002; 1999; 1996; Joseph, 1999). Is Cameroon’s adherence to the EITI part of a pseudo-democratic scheme? Is it merely aimed at gaining international approval and assistance without any desire for reform? The significant problems affecting the EITI program in Cameroon seem to confirm this opinion. On the basis of the experiences and opinions expressed by the key actors in Cameroon’s oil sector (interviews) and in line with previous studies (Diamond, 2002; 1999; 1996; Joseph, 1999) this thesis argues that Cameroon is an “arche-typical” virtual democracy. It then describes and explains how this mode of political organisation relates to and inhibits the efficacy of the national EITI program. The thesis ultimately suggests proposals - after identifying the various actors with the authority to initiate reforms - for a more efficient and sustainable EITI implementation in this Central African state.